Single cell force spectroscopy of T cells recognizing a myelin-derived peptide on antigen presenting cells - Hoffmann, Sabrina; Hadji Hosseini, Babak; Hecker, Markus; Louban, Ilia; Bulbuc, Nadja; Garbi, Natalio; Wabnitz, Guido H.; Samstag, Yvonne; Spatz, Joachim P.; Hämmerling, Günter J. (Immunology letters, 2011)
T-cell recognition of peptide-MHC complexes on APCs requires cell-cell interactions. The molecular events leading to T-cell activation have been extensively investigated, but the underlying physical binding forces between T-cells and APCs are largely unknown. We used single cell force spectroscopy for quantitation of interaction forces between T-cells and APCs presenting a tolerogenic peptide derived from myelin basic protein. When T-cells were brought into contact with peptide-loaded APCs, interaction forces increased with time from about 0.5nN after 10s interaction to about 15nN after 30min. In the absence of antigen, or when ICAM-1-negative APC was used, no increase in binding forces was observed. The temporal development of interaction forces correlated with the kinetics of immune synapse formation, as determined by LFA-1 and TCR enrichment at the interface of T-cell/APC conjugates using high throughput multispectral imaging flow cytometry. Together, these results suggest that ICAM-1/LFA-1 redistribution to the contact area is mainly responsible for development of strong interaction forces. High forces will keep T-cells and APCs in tight contact, thereby providing a platform for optimal interaction between TCRs and peptide-MHC complexes.
Gesehen am 21.07.2022